Yeast Ist2 recruits the endoplasmic reticulum to the plasma membrane and creates a ribosome-free membrane mcrocompartment - Wolf, Wendelin; Lorenz, Holger; Seedorf, Matthias (PLOS ONE, 2012)
The endoplasmic reticulum (ER) forms contacts with the plasma membrane. These contacts are known to function in non-vesicular lipid transport and signaling. Ist2 resides in specific domains of the ER in Saccharomyces cerevisiae where it binds phosphoinositide lipids at the cytosolic face of the plasma membrane. Here, we report that Ist2 recruits domains of the yeast ER to the plasma membrane. Ist2 determines the amount of cortical ER present and the distance between the ER and the plasma membrane. Deletion of IST2 resulted in an increased distance between ER and plasma membrane and allowed access of ribosomes to the space between the two membranes. Cells that overexpress Ist2 showed an association of the nucleus with the plasma membrane. The morphology of the ER and yeast growth were sensitive to the abundance of Ist2. Moreover, Ist2-dependent effects on cytosolic pH and genetic interactions link Ist2 to the activity of the H+ pump Pma1 in the plasma membrane during cellular adaptation to the growth phase of the culture. Consistently we found a partial colocalization of Ist2-containing cortical ER and Pma1-containing domains of the plasma membrane. Hence Ist2 may be critically positioned in domains that couple functions of the ER and the plasma membrane.